Transformasi Human Capital dan Dynamic Marketing Capability dalam Mendorong Kinerja Pemasaran UMKM - Muhammad Tahajjudi Ghifary; Dyajeng Puteri Woro Subagio; Gandi Aswaja Yogatama; Prasetyo Alif Soeprawiro; Ardyan Wicaksana (Universitas Tabanan, 2026)
Increasingly dynamic business competition demands that Micro, Small, and Medium Enterprises (MSMEs) be able to adapt to market changes and digital technology developments. One important factor determining MSME success is the quality of human resources and the company's ability to implement adaptive marketing strategies. This study aims to analyze the effect of human capital on marketing performance through dynamic marketing capability in MSMEs in East Java. The study employed a quantitative approach using a survey method involving 180 MSME owners who are directly engaged in marketing activities and business decision-making. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that human capital has a positive and significant effect on dynamic marketing capability. Furthermore, dynamic marketing capability was also proven to enhance MSME marketing performance, both in terms of sales growth, market expansion, and customer retention. The findings of this study suggest that developing human resource competencies and adaptive marketing capabilities are key factors in improving the competitiveness of MSMEs in the digital era.